Adverse Events Profile of Low-dose Methotrexate in Nepalese Patients with Rheumatoid Arthritis: an Observational Study - Nakarmi, Shweta; Pudasaini, Kalpana; Adhikari, Bhojraj; Vaidya, Binit (Journal of Nepal Health Research Council, 2020)
Background: Methotrexate is considered as the anchor drug for the treatment of rheumatoid arthritis. However, various adverse effects limit its use leading to frequent discontinuation of treatment. This study aimed to evaluate the common adverse effects of methotrexate in patients with rheumatoid arthritis. Methods: A prospective observational study was conducted at National Center for Rheumatic Diseases from June 2018 to May 2019 among patients with rheumatoid arthritis using methotrexate monotherapy. Laboratory tests like liver function tests, renal function tests, complete blood count, C-reactive protein, erythrocyte sedimentation rate were done at baseline and every 3 months. Data on patients’ comorbidities, disease activity and side effects of drug were collected on every follow- up. Statistical analysis was carried out with the help of SPSS 23.0. Results: Out of 232 patients experiencing at least one adverse effect while on methotrexate monotherapy, 87.5% were female and mean age was 46.9±10.8 years. The mean dose of methotrexate was 16.6 ± 3.9 mg/week with the most frequently used dose of 20mg/week. Among the variety of adverse reaction observed, the most common was transaminitis (75.0%) with approximately 50.0% as isolated liver function abnormality, followed by nausea (19.4%), anorexia (12.9%), leukopenia (12.5%), oral ulcer (8.2%) and psychological intolerance (4.7%). Multiple regression analysis showed significant predictive value of body mass index for transaminitis (p-value 0.007). Conclusions: Asymptomatic liver function test derangement was the most frequent adverse-effect of methotrexate observed, whereas nausea and anorexia were the most common patient reported events. The frequent dose associated with side-effects in Nepalese patients was around 20mg/week. Keywords: Adverse events; methotrexate; Nepal; rheumatoid arthritis